An extended phase Ib study of epertinib, an orally active reversible dual EGFR/HER2 tyrosine kinase inhibitor, in patients with solid tumours. (November 2018) - Arkenau, H.-T.; Italiano, A.; Mak, G.; Toulmonde, M.; Baird, R.D.; Garcia-Corbacho, J.; Plummer, R.; Flynn, M.; Forster, M.; Wilson, R.H.; Tosi, D.; Adenis, A.; et al.
Abstract: Background: Dose-escalation of epertinib (S-222611), a new potent oral EGFR/HER2 inhibitor, has established a recommended daily dose of 800 mg in patients with solid tumours. In this study, we have recruited a larger number of patients to assess further the safety, tolerability, pharmacokinetics (PKs) and antitumour activity. Patients and methods: Patients with solid tumours expressing EGFR or HER2 received a single dose of epertinib at 800 mg on Day 1 to assess PK over 7 days, followed by continuous once-daily dosing from Day 8. Results: We treated 76 patients with breast (n = 27), upper gastrointestinal (GI; n = 30), head and neck (n = 12) or renal cancers (n = 7). Epertinib was well-tolerated with mostly grade I and II adverse events (AEs). The most frequent AE was diarrhoea, which was generally manageable with loperamide. The objective response rate (ORR) in patients with heavily pretreated breast and upper GI cancers was 16.0% (4 PRs) and 8.3% (1CR, 1PR), respectively. All six responding patients had HER2-positive tumours; the ORR for HER2-positive breast and upper GI cancer populations was 19.0% and 20.0%. Partial response in the brain disease of one breast cancer patient lasted 7.5 months. Conclusion: Once-daily dosing of epertinib at 800 mg was well-tolerated and demonstrated promising antitumour activity in patients with heavily pretreated HER2-positive breast and upper GI cancer, including those with brain metastases. EudraCT number: 2009-017817-31. Highlights: Epertinib (S-222611) is a new potent oral inhibitor of EGFR, HER2 and HER4. Seventy-six patients treated, with cancers expressing EGFR or HER2, including breast. Well-tolerated with long-term dosing, predominantly grade I/II adverse events. Response rates in HER2-positive breast and upper GI cancers were 19% and 20%. Breast cancer responses included metastatic brain disease.